ALTERNATIVE ENERGY SYSTEMS: THE ROLE AND DEVELOPMENT TRENDS OF BIOGAS TECHNOLOGIES (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the role of biogas technologies in the alternative energy system, their historical stages of development, and modern development trends. The article covers the initial fermentation processes that arose in ancient China and India based on the processing of organic waste, scientific research conducted in the 17th–19th centuries, and the industrial application of biogas technologies in the 20th century. It also analyzes the development of biogas energy in Europe, the USA, China, and India, its role in the system of renewable energy sources, and the state policy and regulatory framework for the development of this sector in Uzbekistan. The article highlights the importance of biogas technologies in ensuring environmental safety, increasing energy efficiency, and developing a “green economy”.
Keywords: Biogas, anaerobic digestion, methane, renewable energy, alternative energy, biogas plant, green economy, energy efficiency, development trends.